Identification of a Novel CCM1 Frameshift Mutation in a Chinese Han Family With Multiple Cerebral Cavernous Malformations - Zhang, Fan; Xue, Yiteng; Zhang, Feng; Wei, Xiaoming; Zhou, Zhisong; Ma, Zhaoru; Wang, Xiaosong; Shen, Hong; Li, Yujun; Cui, Xiaoying; Liu, Li (Frontiers in Neuroscience, 2020)
Cerebral cavernous malformations (CCMs) are vascular lesions that predominantly occur in the brain. CCMs can be sporadic or hereditary in an autosomal dominant manner. The genes harboring variants of familial CCMs (FCCMs) include CCM1/KRIT1, CCM2/MGC4607 and CCM3/PDCD10. In this study, we identified a novel CCM1/KRIT1 mutation in a Chinese family with FCCMs. This family consists of 20 members and 6 of them had been diagnosed with CCMs. The proband patient is a 17-year-old female who has suffered from CCMs-related intracranial hemorrhage four times. Magnetic resonance imaging (MRI) revealed four lesions in the different brain regions and one lesion has progressively enlarged. The pathological histology confirmed CCMs. Whole exome sequencing revealed a novel deletion mutation (c.1635delA) within exon 15 of CCM1/KRIT1 gene in the proband patient, her mother and her uncle who had CCMs. This frameshift mutation led to a premature termination codon (PTC) at nucleotides 1652 to1654. We also detected that the CCM1 mRNAs levels in the blood lymphocytes of the family members with CCMs were reduced by 46.4% compared to that in healthy controls. Collectively, our results suggested that the CCM1 mutation could potentially be a causative factor for FCCMs in the Chinese family and the reduction of CCM1 mRNA expression in the blood lymphocytes of the patients might be a potential biomarker for the diagnosis and prognosis of CCMs. Our findings expanded the spectrum of CCM mutations and helped to guide genetic counselling and early genetic diagnosis for at-risk family members.